2021
DOI: 10.1038/s42003-021-01651-y
|View full text |Cite
|
Sign up to set email alerts
|

Kaiso (ZBTB33) subcellular partitioning functionally links LC3A/B, the tumor microenvironment, and breast cancer survival

Abstract: The use of digital pathology for the histomorphologic profiling of pathological specimens is expanding the precision and specificity of quantitative tissue analysis at an unprecedented scale; thus, enabling the discovery of new and functionally relevant histological features of both predictive and prognostic significance. In this study, we apply quantitative automated image processing and computational methods to profile the subcellular distribution of the multi-functional transcriptional regulator, Kaiso (ZBT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 88 publications
3
25
0
Order By: Relevance
“…To determine the predictive value of gp78 expression in mammary malignancies, we analyzed a previously established racially diverse breast cancer cohort of patients ( n = 560) residing in a designated health disparities catchment area in Eastern North Carolina (median follow-up, 8.5 years) and arrayed in tissue microarray (TMA) format ( 6 , 11 , 49 , 50 ) to define the association between gp78 protein levels and breast cancer patient tumor characteristics and survival. The expression of gp78 was measured by IHC using a quantitative digital pathology platform in which pathologist-annotated regions of tumor were scored in terms of the IHC staining level assessed by an increasing pixel intensity stratification: 0, 1 + , 2 + , or 3 + ( 6 , 11 , 49 , 51 ). The percent of cells with these intensities were then used to assign protein expression values based on a continuous metric referred to as the H-score (0–300 scale) using the following equation: (H-score = 3 [%3 + ] + 2 [%2 + ] + 1 [%1 + ]) ( 6 , 11 , 49 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the predictive value of gp78 expression in mammary malignancies, we analyzed a previously established racially diverse breast cancer cohort of patients ( n = 560) residing in a designated health disparities catchment area in Eastern North Carolina (median follow-up, 8.5 years) and arrayed in tissue microarray (TMA) format ( 6 , 11 , 49 , 50 ) to define the association between gp78 protein levels and breast cancer patient tumor characteristics and survival. The expression of gp78 was measured by IHC using a quantitative digital pathology platform in which pathologist-annotated regions of tumor were scored in terms of the IHC staining level assessed by an increasing pixel intensity stratification: 0, 1 + , 2 + , or 3 + ( 6 , 11 , 49 , 51 ). The percent of cells with these intensities were then used to assign protein expression values based on a continuous metric referred to as the H-score (0–300 scale) using the following equation: (H-score = 3 [%3 + ] + 2 [%2 + ] + 1 [%1 + ]) ( 6 , 11 , 49 ).…”
Section: Resultsmentioning
confidence: 99%
“…The expression of gp78 was measured by IHC using a quantitative digital pathology platform in which pathologist-annotated regions of tumor were scored in terms of the IHC staining level assessed by an increasing pixel intensity stratification: 0, 1 + , 2 + , or 3 + ( 6 , 11 , 49 , 51 ). The percent of cells with these intensities were then used to assign protein expression values based on a continuous metric referred to as the H-score (0–300 scale) using the following equation: (H-score = 3 [%3 + ] + 2 [%2 + ] + 1 [%1 + ]) ( 6 , 11 , 49 ). Using the Aperio platform, digital scoring for gp78 was strongly correlated with the manual score provided by a pathologist (adjusted Pearson’s R 2 = 0.93) ( Supplemental Figure 1A ; supplemental material available online with this article; https://doi.org/10.1172/jci.insight.157465DS1 ).…”
Section: Resultsmentioning
confidence: 99%
“…These results demonstrate that Kaiso-14-3-3σ interaction may be dependent on the Kaiso-P120ctn binding and that Kaiso, 14-3-3σ, and P120ctn may form a triplex in the cytoplasm. It was reported that cytoplasm Kaiso functionally linked the autophagy-related protein LC3A/B in breast cancer cells (55). How Kaiso, 14-3-3σ, and P120ctn interacting with each other is worth further studying.…”
Section: Discussionmentioning
confidence: 95%
“…Uhrf1-mediated tnf-α gene methylation controlled proinflammatory macrophages in experimental colitis resembling inflammatory bowel disease ( Qi et al, 2019 ). In breast cancer, ZBTB33 subcellular partitioning functionally linked LC3A/B, the tumor microenvironment, and cancer survival ( Singhal et al, 2021 ). These results indicated that the 5mC modification is intimately involved in shaping TME landscapes.…”
Section: Discussionmentioning
confidence: 99%